2007
DOI: 10.1155/2007/296049
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric Determination of Fenpropathrin in its Formulations and Water Samples

Abstract: Novel spectrophotometric methods were developed for the determination of fenpropathrin in insecticidal formulations and water samples. The methods were based on the hydrolysis of fenpropathrin with ethanolic KOH to form 3-phenoxy benzaldehyde. The resultant aldehyde group was condensed with anthranilic acid in presence of basic medium to form yellowish red color product having λ max of 485 nm or condensed with 2-chloro phenyl hydrazine to form pink color product having λ max of 557 nm. The color derivatives we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 3 publications
0
4
0
Order By: Relevance
“…Solvent selection for the extraction of environmental samples has been described [67]. A single solvent or a mixture of two solvents have been tested for extraction of pyrethroids from environmental samples [68][69][70][71][72][73]. Most commonly used solvents were dichloromethane (DCM), n-hexane, toluene, and ethyl acetate.…”
Section: Liquid-liquid Extraction (Lle)mentioning
confidence: 99%
See 1 more Smart Citation
“…Solvent selection for the extraction of environmental samples has been described [67]. A single solvent or a mixture of two solvents have been tested for extraction of pyrethroids from environmental samples [68][69][70][71][72][73]. Most commonly used solvents were dichloromethane (DCM), n-hexane, toluene, and ethyl acetate.…”
Section: Liquid-liquid Extraction (Lle)mentioning
confidence: 99%
“…Soxhlet extraction and related techniques have been used as referee methods when conventional procedures based on other principles have to be evaluated [70,87]. These conventional methods have in common with soxhlet, the fact that they are time-consuming and require a large amount of solvents.…”
Section: Soxhlet Extraction (Sxe)mentioning
confidence: 99%
“…Absorption spectra: After alkaline hydrolysis cypermethrin and fenvalerate react with potassium iodide in acidic Effect of time and temperature: Hydrolysis of cypermethrin and fenvalerate to cyanide ion was studied at different temperatures. It was observed that the maximum hydrolysis was obtained with 20 % of sodium hydroxide at temperature range of 30-40 °C as it gave maximum absorbance values with good stability [23,25] (Fig. 3).…”
Section: Resultsmentioning
confidence: 91%
“…Determination of cypermethrine and fenvalerate in agricultural runoff water: Agricultural runoff water from river of Rajim Kumbh, Raipur district (Chhattisgarh) was collected in glass bottle (amber). Interferences of chloride ions and humic acid first suppressed by adding 1 mL of 0.1 M Na2S2O3 solution in 1 L of water sample [25]. After that this solution was filtered and an aliquots of water samples were taken in 25 mL calibrated tube and added sodium hydroxide and kept in hot water bath for completion of hydrolysis.…”
Section: Effect Of Phmentioning
confidence: 99%